Peran Inovasi Produk dan Citra Merek Dalam Mendorong Pembelian Berulang - Johan Rizki A; Nikolas Maro Sepoetro; Sheva Nabilio (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the current era of globalization, fashion products are one of the products that are quite in demand by consumers after food. In the past, clothing or fashion was a mere primary need. Along with the development of the clothing, entertainment, technology and information industries, fashion style is a medium for users to be able to increase their confidence, look fashionable and can support lifestyle. According to Fatmawati et al. (2017), fashion or fashion is the application of a person's way of wearing clothes, accessories, or even in the form of hairstyles to makeup that can be seen through a person's lifestyle. The fashion industry is one of the largest contributors to the 14 creative industries in Indonesia. This shows that the Indonesian people are well aware of looking attractive and stylish by following the development of emerging fashion trends. Along with the development of the fashion business, the company's competition to obtain profits and consumer loyalty is also increasing. Keywords : , ,